L. KARSAVINO ISTORIOSOFINIS MESIANIZMAS IR EURAZIJOS IDĖJA - Mažeikis, Gintautas (Problemos, 2008)
Straipsnyje analizuojamos Karsavino Eurazijos ir simfoninės asmenybės teorijos ir jų įtaka asmeniniam Karsavino likimui, jo sofiologinėms mesianistinėms nuostatoms. Aptariama svarbiausių filosofinių Karsavino idėjų genezė: gyvo religingumo ir bendrojo religinio fondo, gnostinės pleromos interpretacijos, Šv. Trejybės dialektika ir jos santykis su N. Kuziečio filosofija, simfoninės asmenybės teorija. Pagrindinis teiginys apie Karsavino ir Kuziečio filosofijų skirtumą yra pagrįstas kristologiniais Karsavino argumentais apie Kuziečio filosofijos nepakankamumą aiškinant Dievo kaip Possest eksplikacijos ir komplikacijos problematiką. Karsavinas, remdamasis ortodoksiniais kristologiniais teiginiais, simfoninės asmenybės bei ideokratijos teorija bei tipologine, istoriosofine civilizacijų klasifikacija, pagrindžia kairiąją Eurazijos sąjūdžio ideologiją, kuri išliko aktuali ir šiandienos Rusijos politinei situacijai. Straipsnyje parodomos lietuviškosios filosofijos ir Karsavino samprotavimų paralelės ir keliamas klausimas dėl Eurazijos ideologijos nesvarstymo tarpukario Lietuvoje. Straipsnio pabaigoje grįžtama prie filosofinio Karsavino apsisprendimo, saikingų, asmeninių mesianistinių jo nuostatų ir sokratiško likimo tardymų, įkalinimo Abezės lageryje laikotarpiu. Pagrindiniai žodžiai: gyvasis religingumas, simfoninė asmenybė, panteizmas, gnoticizmas, mesianizmas.Historiosophical Messianism of L. Karsavin and the Idea of Eurasia Gintautas MažeikisSummaryThe historiosophical and messianistic ideas of L. Karsavin and his ideology of left Eurasia were based on the theological and gnostic symbolism of the early 20th century, F. Schelling’s philosophy of Myth and Universality, Vl. Solovjov’s Philosophy of Universality, Mystics of Christology, the Orthodox understanding of Saint Trinity, typological theory of civilizations. At the beginning of his mediaeval researches Karsavin investigated sacral events in rural areas in the 17th–18th centuries, especially in Italy, magic activities and popular beliefs in Christian Saints, based on uncritical, natural, live religious feelings and spontaneous faith. He maintained live religious faith to be the background for the significance and utility of all canonical religious rules and churches. These ideas are similar to the French school of Annales and to the M. Bakhtin’s theory of Carnival issues of the Mediaeval tradition of laughter. However, Karsavin re lated his consideration of spontaneous hierophany to the gnostic tradition of Divine Pleroma. It is important to them in order to interpret the philosophy of Nicolaus Cusanus, especially his conception of God as Possest and a permanent and contradictory process of explicatio and complicatio. On the basis of Cusanus’ philosophy, Karsavin developed his personal idea of dialectics of Saint Trinity as a union of Divine personalities. Karsavin maintained that the conception of Cusanus is insufficient because Cusanus didn’t explain the role of Christ in the full reunification of sinful human beings with God. By Karsavin, Cusanus avoided pantheistic tendencies and therefore couldn’t develop the theory of divination of personality. On the contrary, Karsavin develops the idea of divination of oneself in his theory of Symphonic personality. Every personality is a form of free solution and responsibility, love and self-sacrifice. Therefore, the personality develops itself from an autonomous individual into the personality as a family, the personality as a nation, as a state, and finally the personality transforms into a cosmic human being, or Adam Kadmon. The hierarchic growth of personality, his ontology presupposes his essential responsibility for the development of nation, state, culture and civilization. It was the basis of Karsavin’s messianism. The nation or culture couldn’t be developed in the necessary direction, towards divinity, without creative and self-sacrificing activity of the individual. The hierarchical conception of the world personality presupposes the ideocratic form of government. The idea of the ideocratic power makes Karsavin’s political considerations similar to the Soviet system of power. Karsavin from 1925 until 1929 was the leader of the left wing of the Eurasia movement which was located in Paris. He initiated and supported a dialog with Bolsheviks’ representatives. However, Karsavin strongly criticized communism and Bolsheviks from the Orthodox point of view. Karsavin was a deep believer and couldn’t support the destruction of churches by the Soviet regime. However, today it is possible to say that Karsavin’s political visions are very similar to the modern Vl. Putins’ regime in contemporary Russia. Eurasia and Symphonic Personality ideas became important motives for Karsavin’s coming to Lithuania in 1928. However, after arrival he didn’t participate in any political movement and developed his civilization ideas, the conception of ideocratic power and Symphonic Personality there. In the Lithuanian period, he becomes closer to the Russian Orthodox tradition of Old Believers and its ideas of self-sacrifice to populace. Karsavin didn’t emigrate from Lithuania in the threat of Soviet occupation. On the contrary, he spread his ideas of Symphonic Personality, dialectics of Trinity, self-sacrificing after the War and even in the concentration camp in Abeze until his death in 1952. Keywords: live religions, Symphonic Personality, pantheism, gnosticism, messianism.-size: 11pt;">